Current Issues and Challenges in the Use of Aerosolized Surfactant for Respiratory Distress Syndrome in the Newborns - Dion Darius Samsudin (The Indonesian Biomedical Journal, 2013)
BACKGROUND: Surfactant replacement therapy is a recognized treatment for respiratory distress syndrome (RDS) in the newborns. Over the past 30 years, human and animal trials have been performed regarding administration of aerosolized surfactant to the injured lung, however the result has been unsatisfactory when compared with instilled surfactant delivery via endotracheal tube (ETT). This review aims to investigate the current issues, challenges and future recommendation of aerosolized surfactant therapy.CONTENT: Five randomized clinical trials in humans and 13 animal trials met the inclusion criteria and were reviewed. Most animal trials agree that this method of treatment is feasible. However, human trials presented conflicting results, and generally showed it to be ineffective. When compared with surfactant delivery via ETT, aerosolized surfactant is less effective in improving respiratory function.SUMMARY: The current data from human trials does not support the implementation of aerosolized surfactant therapy to treat newborns with RDS. Further research is necessary to improve nebulization, delivery, distribution and deposition in the lung, to investigate aerosolized surfactant delivery via ETT and to determine the appropriate dose.KEYWORDS: surfactant, aerosol, prematurity, respiratory distress syndrome